2009
DOI: 10.1143/jjap.48.126502
|View full text |Cite
|
Sign up to set email alerts
|

Kinematical Modeling of Pad Profile Variation during Conditioning in Chemical Mechanical Polishing

Abstract: Conditioning is the process of removing the glazing area from a polishing pad surface and restoring the quality of the surface to maintain a stable polishing performance. However, the conditioning process can induce a non-uniform profile variation of the pad, which can result in nonuniform material removal rates across the wafer. In this paper, a kinematical model based on Preston's equation is proposed to examine the pad profile variation (PPV) induced by swing arm conditioning with a diamond disk. The propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Many researchers have used kinematic analysis to investigate the conditioning process [5][6][7][8]. However, almost all the above research studies are about the soft pad, not the fixed abrasive pad.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers have used kinematic analysis to investigate the conditioning process [5][6][7][8]. However, almost all the above research studies are about the soft pad, not the fixed abrasive pad.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They explained that the difference between experimental result and simulation may come from the moment that the friction forces act on the conditioner disk. Lee et al [35] simulated swing-arm CMP conditioning via kinematic modeling and showed that the swing-arm velocity profile (SAVP) affected the pad profile. They calculated the pad wear profile by drawing a virtual concentric circle on the surface of the pad and summing the sliding distance of the conditioner's diamond grits passing through the virtual area.…”
Section: Introductionmentioning
confidence: 99%
“…The pad wear rate is affected by many factors [28,29] [103] have studied a kinematical model of motions of the conditioner in the CMP process; however, the conditioner in their research is handled by a swing arm, not an oscillation motion in the radial direction. Chang et al [101] have also proposed a mathematical model based on a kinematic motion but they assumed that "the oscillation velocity is neglected".…”
Section: Pad Wear Profilementioning
confidence: 99%
“…In CMP processes, pad wear has an important effect on the uniformity of wafer substrates. If the pad wear is not uniform, the cutting effect of the pad on the wafer surface is also not uniform [28,103]. The pad is almost concave which results in the non-uniformity of polished surfaces.…”
Section: Improvement Of the Non-uniformitymentioning
confidence: 99%
See 1 more Smart Citation